(untitled) (Revista de Ciências Agroveterinárias, 2005)
The native and naturalized fields present low productivity. Phosphate fertilization is one of the key strategies to improve the production and persistence of pastures with legumes. An experiment was carried out aiming to evaluate the effect of a national rock phosphate (FN) in comparison with the soluble triple superphosphate on the establishment and initial development of a perennial winter pasture. The experiment was installed in São José of Cerrito/SC, on an Oxisol. A completely randomized block design with four replications was used. Treatments were constituted as follows: control - without lime and fertilizer; correction of the phosphorus needs with the use of 417 kg/ha rock phosphate (only FN); limestone application for pH 5,2 and correction of phosphorus needs with the use of 333 kg/ha rock phosphate (FN) and 50 kg/ha triple superphosphate (CAL+FN+ST); limestone application for pH 5.2 and correction of the phosphorus needs with the use of 417 kg/ha rock phosphate, considering total P 2 O 5 of the rock (CAL+FN1); limestone application for pH 5.2 and correction of the phosphorus needs with the use of 1,333 kg/ha rock phosphate, in a dose of ¼ of the amount of soluble P 2 O 5 in citric acid (2%) (CAL+FN2); limestone application for pH 5.2 and correction of the phosphorus needs with 244 kg/ha triple superphosphate (CAL+ST). The quantity of 7.66 Mg/ha of dolomitic limestone was used to reach to pH 5.2. Six cuts were performed in an interval of 45 days to estimate the production of pasture dry mass. Two soil sampling were performed to determine the chemical attributes of the soil. The isolated use of rock phosphate was not advisable to install perennial pastures in the tested area. The association between liming and different sources of phosphate (rock phosphate and/or triple superphosphate) was efficient in the implantation of those pastures. The red clover and the birtsfoot were the most favored species with the soil conditions created by the limestone and phosphorus addition.